Epigenetic regulation of rice flowering and reproduction - Shi, Jinlei; Dong, Aiwu; Shen, Wen-Hui (Frontiers in Plant Science, 2015)
Current understanding of the epigenetic regulator roles in plant growth and development has largely derived from studies in the dicotyledonous model plant Arabidopsis thaliana. Rice (Oryza sativa) is one of the most important food crops in the world and has more recently becoming a monocotyledonous model plant in functional genomics research. During the past few years, an increasing number of studies have reported the impact of DNA methylation, noncoding RNAs and histone modifications on transcription regulation, flowering time control and reproduction in rice. Here we review these studies to provide an updated complete view about chromatin modifiers characterized in rice and in particlar on their roles in epigenetic regulation of flowering time, reproduction and seed development.